Baseline predictors for progression 4 years after Parkinson's disease diagnosis in the De Novo Parkinson Cohort (DeNoPa). Issue 1 (23rd November 2018) - Mollenhauer, Brit; Zimmermann, Johannes; Sixel‐Döring, Friederike; Focke, Niels K.; Wicke, Tamara; Ebentheuer, Jens; Schaumburg, Martina; Lang, Elisabeth; Friede, Tim; Trenkwalder, Claudia; ,
Abstract: Objectives: The objectives of this study were to investigate (1) the annual rate of progression of motor and cognitive symptoms and (2) baseline predictors of different modalities for this progression in early Parkinson's disease (PD) when compared with healthy controls. Methods: A total of 135 de novo PD and 109 healthy controls (of the De Novo Parkinson cohort) were investigated at baseline and after 24 and 48 months. To delineate motor progression and cognitive decline, the Movement Disorder Society‐Unified Parkinson's Disease Rating Scale part III (MDS‐UPDRS III) and the Mini‐Mental Status Examination (MMSE) were selected. Baseline variables used to predict progression included sociodemographic factors, comorbidities, motor/nonmotor symptoms, polysomnography, MRI, and laboratory biomarkers in serum and CSF. Results: Symptoms worsened over 4 years in PD with an annual change of 1.8 points on the MDS‐UPDRS III and 0.2 points on the MMSE. Baseline predictors of worse progression of motor symptoms in PD included male sex, orthostatic blood pressure drop, diagnosis of coronary artery disease, arterial hypertension, elevated serum uric acid, and CSF neurofilament light chain. Predictors of cognitive decline in PD included previous heavy alcohol abuse, current diagnoses of diabetes mellitus, arterial hypertension, elevated periodic limb movement index during sleep, decreased hippocampal volume by MRI, higher baseline levels of uric acid, C‐reactive protein, high density lipoprotein (HDL) cholesterol, and glucose levels. Conclusion: Cardiovascular risk factors, deregulated blood glucose, uric acid metabolism, and inflammation were identified as risk markers for faster disease progression. Our panel of risk parameters needs validation during our continuing follow‐up and also in independent patient cohorts. © 2018 International Parkinson and Movement Disorder Society